Synopsis of the Species of Coccidians Reported in Marine Fish - Aurélia Saraiva; Jorge C. Eiras; Cristina Cruz; Raquel Xavier (Animals, 2023)
Eimeriid coccidians represent one of the largest groups of parasitic unicellular organisms and comprise many species of veterinary and medical importance. The aim of this work is to provide information, as complete as possible, concerning the oocyst phase of the species of coccidians (Apicomplexa: Eimeriorina) with four sporocysts, which were reported in marine fish. For each species, the accepted scientific name and respective authorities, its synonyms, reported hosts, site of infection (organ), and geographic distribution have been assembled. Available information on morphology (oocyst, sporocyst, and sporozoite) and GenBank accession numbers were also compiled. A total of 100 species of coccidians were described and reported from 60 families of marine fishes. Most species have been described from marine teleosts, with only 14 of the species described from marine elasmobranchs. Most of the species reported in marine fish belong to the genera Eimeria and Goussia, and only a handful belong to the genera Epieimeria, Calyptospora, and Crystallospora. Although marine coccidians have began to be described for more than one century, the collection of genetic data on marine fish coccidians only started in the 2010s and remains largely disconnected from the morphological analysis of specimens, which is available for only six formally described species.